Restoration of forests in boreal Sweden - Nordlind, Erik (2005)
Sweden's boreal forest has suffered from radical human caused changes since the beginning of industrialisation. Ecological qualities, such as large trees, dead trees, and deciduous trees, have been removed from the forest. Natural processes, like fire, have been suppressed leading to ecosystem degradation, even in the forest reserves. Many species that directly or indirectly depend upon natural structures are disfavoured and the restoration need is evident. In this study, the present status of a Swedish boreal forest is analysed in a biodiversity restoration context. Based on ecological qualities of a historic reference state, a restoration gap analysis is produced. Methods to recreate lost ecological qualities are discussed. Also, the efficiency of four methods to kill trees and thus increase deadwood, is tested. These methods are: clobbering, girdling, topping with explosives and inoculation of wood-rotting fungi. A gap-analysis is one way to view forest degradation and measure its deviation from the reference state. Ecological qualities are relatively high in this area as compared to the region as a whole, mainly because of recent logging in the region. However, if compared with the reference state, the area has lost a great deal of ecological qualities due to human activity. To be successful, strategies for restoring a degraded forest should ultimately have a landscape level approach. Therefore, restoration of ecological qualities not only includes reserves but also production forests. In production forests, forest management should be adapted to the natural functioning of the ecosystem. Fire is the most important natural process in this ecosystem. Fire-reintroduction and management is the primary goal in the restoration process. Although, it should be complemented by other methods. Clobbering and girdling were the most time-efficient methods to kill trees and did not substantially differ from each other. Topping and inoculation were much less time-efficient. They are also more technically complicated and thus more costly. Due to lack of dead wood in the forest, clobbering, girdling and topping are recommended methods to be used at this time. Whereas, inoculation of wood-rotting funge should be more thoroughly tested. Larger studies, with repeated sample plots in different stand types, must be implemented to gather more data for precise management recommendations. Because of dramatic losses of old growth characters during the last centuries, it is imperative that restoration of old-growth characters is accomplished as well as retaining residual old-growth characters.